Pixinguinha e Dino Sete Cordas: reflexões sobre a improvisação no choro - GEUS, José Reis de (2009)
Choro consists of a musical movement expressing the popular culture of Rio de Janeiro city, originated around 1870, connected with a gradual process of brazilianization that is, an interpretation style of playing European genres with large use of syncope, played for dance. Choro turned into a musical genre on the first decades of the 20th century, until the Radio Era (here understood as the 1930-45 period), based on an instrumental formation called conjunto regional . Among many groups, there was the Regional de Benedito Lacerda (Lacerda´s Group), which had as its integrants, Pixinguinha and Dino Sete Cordas, the focus of this work. Through the transcription and analysis of the recordings played by Lacerda´s Group in the album entitled Benedicto Lacerda e Pixinguinha (released in 1966 with recordings made between 1946-1951) it was possible to verify the melodic lines and performance style of Pixinguinha´s saxophone and his influence on the seven-string-guitar player Dino Sete Cordas in the album entitled Choros Imortais (1964), recorded by Altamiro Carrilho with Regional do Canhoto (Canhoto´s Group). Pixinguinha s performance on the recordings was based on pre-established improvisations possibly due to recording limitations. Dino Sete Cordas was very close to Pixinguinha and also had him as a model. Because of this contact, among other factors, Dino Sete Cordas came up with a characteristic interpretation style, and individual performance concept and a performance school which influenced countless musicians and contributed for a systematization of seven-strings-guitar´s study